Penggunaan Metode Penilaian Trauma Dalam Memprediksi Luaran Pasien : Literatur Review - Ristina Fauzia Hernaningrum; Masfuri Masfuri; Liya Arista; Riri Maria (Jurnal Ners, 2025)
Background: Trauma is one of the causes of morbidity and mortality in the world. Deaths due to trauma in Indonesia are primarily victims of productive age, so it can affect family stability. Initial assessment in the Emergency Unit is an important process that can affect the patient's long-term care outcomes. It requires speed and accuracy in identifying the severity of trauma to be able to immediately determine the priority of treatment and the appropriateness of resources. Objective: To determine the method of assessing the severity of trauma that can be used to predict outcomes in trauma patients. Method: A systematic review was conducted by searching for articles in the database with predetermined keywords, which was then continued with checking, removing duplications, and filtering the content so that six articles were obtained for review. Results: From the various trauma assessments used, it is known that TRISS is the best model that can predict outcomes in the form of mortality in trauma patients. Conclusion: TRISS is the most sensitive trauma assessment method in predicting potential mortality in trauma patients.